Penerapan Bimbingan Belajar Dalam Meningkatkan Kemampuan Guru Menggunakan Teknologi Komputer Dalam Mengajar di SD Negeri 035 Indrapuri - Rahayu, Wastuti (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
The use of technology for a teacher is now a must, teachers who have the ability to use computer technology will easily get and develop learning strategies to learners. There are many other conveniences that teachers get when they master the computer. Speed and efficiency in work will be greatly felt. Using classroom action research, it was found that with the application of tutoring to teachers in improving the ability to use computer, it can be guided learn can improve the ability of teachers using computer. The model of intensive learning guidance and continue to home the use of completion of teacher administration task in the form of reports needs to be done with computers at home. Keywords: Tutoring, Master's Ability, Computer Technology